2016
DOI: 10.1103/physrevb.94.224203
|View full text |Cite
|
Sign up to set email alerts
|

Structural origins of the boson peak in metals: From high-entropy alloys to metallic glasses

Abstract: The boson peak appears in all amorphous solids and is an excess of vibrational states at low frequencies compared to the phonon spectrum of the corresponding crystal. Until recently, the consensus was that it originated from "defects" in the glass. The nature of these defects is still under discussion, but the picture of regions with locally disturbed short-range order and/or decreased elastic constants has gained some traction. Recently, a different theory was proposed: The boson peak was attributed to the fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 55 publications
1
26
0
Order By: Relevance
“…(see Ref. for a review). Nonetheless, the widely accepted opinion is that the BP originates from certain “defects” of glass although their nature is not well understood …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(see Ref. for a review). Nonetheless, the widely accepted opinion is that the BP originates from certain “defects” of glass although their nature is not well understood …”
mentioning
confidence: 99%
“…These “defects” are often understood as free volumes and “soft spots”, i.e., regions of reduced short‐range, lowered elastic moduli and mechanical strength . An interesting study addressed to the BP nature was recently performed by Brink et al who analyzed computer models of a four‐component CuNiCoFe alloy alternatively with chemical disorder (high‐entropy state), structural disorder, and reduced density. They found that density reduction and fluctuations of the elastic constants cannot be responsible for the BP.…”
mentioning
confidence: 99%
“…The per-atom shear moduli were calculated as described in Ref. 54: Different stress states were applied at 0 K and the stiffness tensor calculated with Hooke's law from the strain response for every atom using ovito's atomic strain analysis [57]. Diagonalisation of this tensor yields five shear moduli [55].…”
Section: Appendix D Analysis Of the Elastic Propertiesmentioning
confidence: 99%
“…The models suggested for the interpretation of the BP can be divided into two groups (for a review, see refs. ). First of all, it is most often assumed that the BP originates from certain “defects” of the glassy structure, which are related to locally disturbed short‐range order and/or decreased elastic constants .…”
mentioning
confidence: 97%
“…An important study of the BP was recently reported by Brink et al They performed molecular dynamic simulation of a four‐component CuNiCoFe alloy alternatively with chemical disorder (high‐entropy state), structural disorder, and reduced density. They found that the density reduction, fluctuations of the elastic constants and shift of the van Hove singularity cannot be responsible for the BP.…”
mentioning
confidence: 99%